The Development of Hadith Study in Islamic Boarding Schools and Islamic Higher Education in Indonesia - Yuliharti, Yuliharti; Rahman, Rahman; Nafisah, Lailiyatun; Ridwan, Wawan Ahmad; Ali Akbar, Muhammad Yudi; Alfiah, Alfiah; Nurhaidah, Siti Nuri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The study of hadith as a source of Islamic teachings after the Qur’an is an important part of Islamic studies in Indonesia, both in Islamic boarding schools (pesantren) and Islamic higher education. The study of hadith at these two Islamic educational institutions has a different style. Hadith studies in pesantren are more focused on understanding the content of text (matan) of hadith by studying the traditions contained in the books of Riyad al-Salihin, Sahih al-Bukhori, Sahih Muslim and other books. Meanwhile, the study of hadith in Islamic higher education has experienced rapid development by focusing on the study of methodological mastery, for example, sanad and matan research methodologies. The books that are used as references are also more varied, such as the book of the tarikh al-ruwat, al-jarh wa al-ta'dil, rijal al-hadith, and other contemporary hadith books. This study aims to comprehensively reveal the development of hadith studies in these two Islamic educational institutions. This type of research is field research (field research). The data were collected by conducting a direct search in the field through the methods of interview, observation, and documentation. The data collected were analyzed and presented in a qualitative descriptive manner using a phenomenological approach. The research found that the study of hadith in Islamic boarding schools and Islamic higher education had different tendencies. These two tendencies need to be mapped so that they can be used as a model in comprehensively studying the Prophet's hadith.